KESADARAN TEOLOGI IRSHAD MANJI : STUDY ANALISA EKSISTENSIALIS JEAN PAUL SARTRE - Faridahh, Umi (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2021)
This research examines the thoughts of Ershad Manji using the analysis knife of a philosophical figure, namely Jean Paul Sartre. The objectives of this study are the issues that are the subject of discussion: 1) Knowing the theological awareness of Ershad Manji; and 2) Knowing Jean Paul Sartre's analysis of the theological awareness of Irshad Manji. This research is a library search research and quantitative research. The findings in this research show that: First ,. Irshad Manji is a staunch muslim, provides constructive criticism, and is very supportive of the progress of Islam. The awareness possessed by Irshad Manji brings the concept of Ijtihad back to Islamic thought and avoids thinking in Islam by implementing wall street and moral change. Second, the theological awareness of Irshad Manji is an existentialist concept, the analysis knife of jean paul satre is used to dissect the thought of Irshad Manji. Examining the whole discussion of Irshad Manji brings existentialist values to life through theological awareness...Â